Paraspinal plexiform schwannoma of unknown nerve origin: A case report. (February 2021) - Pace, Spencer; Sacks, Marla A.; Minasian, Tanya; Hashmi, Asra; Khan, Faraz A.
Highlights: Plexiform schwannomas are exceedingly rare in paediatric populations. This is a unique case located outside the spinal canal without a nerve of origin. Preoperative planning is imperative for complete resection and cosmesis. Abstract: Introduction and importance: Schwannomas are benign, slow-growing nerve sheath tumors of neoplastic Schwann cells. They are the most common peripheral nerve tumors in adults and are typically discovered incidentally due to their asymptomatic presentation. Despite the fact that most schwannomas are unassociated with a syndrome, their etiology is thought to be related to alterations or loss of the neurofibromatosis type two tumor suppressor gene. Case presentation: We present the case of a fifteen-year-old female who presented with a recurrent lower back/upper buttocks 9 cm mass with imaging suspicious for schwannoma. Needle biopsy revealed an S100 positive cellular schwannoma with patchy Ki-67. During surgical dissection down to the sacrum, no nerve of origin was identified. Clinical discussion: Schwannomas have no pathognomonic findings on MRI and may occur at any location that Schwann cells are present; therefore, confirming a diagnosis relies on histopathology. Plexiform schwannomas are defined by a "network-like" intraneural growth pattern and are exceedingly rare in paediatric populations. A location distinct from the spinal canal is also very rare as schwannomas typically originate from the head and neck region. Conclusion: Paediatric plexiform schwannomas have been rarely reported. Surgical planning relies on multiple factors such as tumor size, tumor location, pathologic features and symptomatic burden. The distinctive features of this case including an unknown nerve origin and a location outside the spinal canal provide a unique opportunity to discuss the diagnosis and management of paraspinal schwannomas and the impact on operative planning when a nerve of origin is not identified.